Changes during the weathering of polyolefins. (November 2020) - Grause, Guido; Chien, Mei-Fang; Inoue, Chihiro
Highlights: A comprehensive review on the reactions causing degradation during weathering and photo-oxidation. Norrish reactions cause chain scission, but do not initialize photo-oxidation. Radicals form in the presence of oxygen oxidation products and in the absence cross-links. Gel formation is often not regarded during the determination of the molecular weight. A detailed description of the effects of weathering on polymer properties is given. Abstract: Polyolefins are subject to chemical changes when they are brought in contact with the environment. In the presence of UV-radiation and oxygen, photo-oxidation causes chain scission and cross-linking in polyethylene and polypropylene. This review provides a detailed presentation of the reactions that take place and their effects on the properties of polymers. In this review, radical formation and Norrish reactions are discussed in depth, along with the formation of peroxides and carbonyl compounds. More than a dozen different types of carbonyl compounds can be observed by FTIR. While Norrish reactions are the main reason for chain scission and molecular weight reduction, the initial step of the photo-oxidation may be related to the formation of O2 -polymer charge transfer complexes. Photo-oxidation takes place mainly in the amorphous region of the polymer, and polymers with a high tertiary-carbon content are more affected than those with straight chains. Chain scission occurs only in the presence of oxygen, whereas cross-linking in the absence of oxygen results in gel formation. Weathering conditions include seasonal changes, and the day-and-night cycle has a strong impact on photo-oxidation. The chemical changes occurring during weathering influence crystallinity and the mechanical properties of polyolefins. Most of the fundamental work in this field was published more than 30 years ago. It is necessary for the results of these early studies to be verified by methodologies developed in recent years.